Caracteristique Et Vitesse De Propagation D’une Onde De Maree Semi-Diurne A Inegalite Diurne Au Port Autonome D’abidjan : Incidence De La Morphologie Du Systeme Lagunaire Ebrie - Rokyatou, Samassy; Colette, Akobe Apie; Fosti, Fossi Yannick; Sylvain, Monde; Aman, Angora; Seydou, Sangare (European Scientific Journal, ESJ, 2018)
The autonomous port of Abidjan, qualified as "lung of the Ivorian economy", is ranked first in West Africa and second in Africa, after the port of Durban in South Africa. It is a transhipment and container port, thanks to the Vridi channel with a depth of 15 m, the boats with deep draft can dock in deep water. Thus for the safety of the port navigation, it is important to know the speed of propagation of the tidal wave in order to know exactly the tide times in all parts of the Ebrié lagoon. This lagoon in connection with inflows of external waters considerably modify its hydrodynamism. For a mastery of the hydrodynamics of this complex environment we have subdivided the lagoon into three parts depending on the different inputs (fluvial / marine) or not. As a result, the tidal wave spreads much faster in the western part with a speed of 0.83 ms-1 over 1 km, than in the eastern part of the Ebrié Lagoon, is a speed of 0.38 m.s-1. It is also slowing down in the Vridi Channel 0.79 m.s-1. Thus the propagation of the tidal wave in the lagoon would be hampered by fluvial inputs and also by a restricted basin such as the Vridi Canal. In addition, the marine influence is dominant in the dry season, however in high flood season the tide phenomenon is more important in the lagoon. The ebb tide is faster and longer than the lagoon flow, but the reverse phenomenon is observed at sea.